Ethnic Spatial Dispersion and Immigrant Identity - Amelie F. Constant; Simone Schüller; Klaus F. Zimmermann (Center for Economic Studies and ifo Institute (CESifo), 2023)
The role of ethnic clustering in ethnic identity formation has remained unexplored, mainly due to missing detailed data. This study closes the knowledge gap for Germany by employing a unique combination of datasets, the survey data from the German Socio-Economic Panel and disaggregated information at low geographical levels from the last two but still unexploited full German censuses, 1970 and 1987. Utilizing the exogenous placement of immigrants during the recruitment era in the 1960s and 1970s we find that local co-ethnic concentration affects immigrants' ethnic identity. While residential ethnic clustering strengthens immigrants' retention of an affiliation with their origin (minority identity), it weakens identification with the host society (majority identity). The effects are nonlinear and become significant only at relatively high levels of co-ethnic concentration for the minority identity and at very low levels of local concentration for the majority identity. The findings are robust to an instrumental variable approach.
Keywords: J15; R23; Z10; 330; ethnic minorities; residential segregation; ethnic identity; spatial dispersion; ethnic clustering; ethnic enclaves